HISTOMORPHOMETRY OF AGRANULOCYTE WHITE BLOOD CELLS OF BALI CATTLE IN NUSA PENIDA - Adinugroho, M. Oenas; Suwiti, Ni Ketut; Kendran, Anak Agung Sagung (Buletin Veteriner Udayana; Vol. 11 No. 1 Pebruari 2019DO - 10.24843/bulvet.2019.v11.i01.p06, 2019)
This study aims to determine about the histology structure and the morphometry white blood cells agranulocytes (lymphocytes and monocytes) of Bali cattle in Nusa Penida. A sample of blood from 50 female calves, had been taken through a jugular vein. The blood samples were fixed and colored by using Giemza staining method. The morphometry measurement was performed with was done under Axio Zeiss Imager 2 microscope with 1000x magnification. The results of the measurements were analyzed descriptively quantitatively, while the histology description was analyzed by qualitative descriptive. The results showed average mean lymphocyte diameter (9.22 ± 0.73µm) was smaller than monocytes (12.48 ± 1.73 µm). The existence of the lymphocyte and monocytes histologic structure difference which are found in the nucleus. The lymphocyte nucleus was round and filled the cytoplasm, whereas the monocyte nucleus formed a curve on one or two sides, thus, it did not fill the cytoplasm.